The Economic and social role of the merchant Hashim Yousef Al-Awadi (1918-1991) In the Emirate of Ras Al Khaimah - AlAlayli, Khawla; Al-Awadhi, Hamda (Al-Adab Journal, 2024)
The economy of the United Arab Emirates, before the establishment of the Union on December 2, 1971 AD, was built on the shoulders of a class of merchants who contributed to supporting its economy through their participation in financing the pearl trade, the most important trade in the Arabian Gulf, and the import and export trade with various Asian and African countries. They were the pillar of Essential and indispensable to ensure the continuation of the economy of their countries.The merchant Hashem Yousef Al-Awadhi is considered one of those important figures in establishing vital and modern economic projects in a remote border area. He contributed to improving the life quality for the people of that remote area. Simultaneously, he contributed to the treasury of the Ras Al Khaimah Emirate government during the most challenging economic conditions after the failure of the pearls trade and the outbreak of The Second World War (1939-1945). His contributions to the economic sector included establishing a station to supply fossil oil, establishing the Al-Huwailat Customs Center, and working in the tobacco trade. Merchant Hashem was able to finance and obtain the right to export tobacco to the local and Gulf markets, obtaining close commercial relations with a group of Arabian Gulf merchants.This study focused on conducting personal interviews with some members of the merchant Hashim Yousef Al-Awadhi's family and some of his contemporaries. Furthermore, this study analyzed several official documents issued by the Ras Al Khaimah government, which the family of the merchant Hashim Yousef Al-Awadhi preserved.